2021
DOI: 10.3390/ijerph18041885
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Social Media Use and Health among Adolescents

Abstract: (1) Background: The use of social media has become an integral part of adolescents’ daily lives. However, the intensive use of social media can develop into a health-threatening addiction, but unfavourable health consequences can occur even with less use. Social media user groups categorized as no-risk, moderate risk (of developing problematic behaviour), and problematic use were examined with reference to their prevalence, their associations with individual determinants and health, and the increased health ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
49
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 49 publications
7
49
1
3
Order By: Relevance
“…The same study found that there was no association between family affluence and PSMU [19]. Findings on the relationship between gender and PSMU are varied; Bányai et al (2017) and Kircaburun et al (2019) found that girls are at a higher risk of PSMU than boys, whereas Paakkari et al (2021) did not find gender differences for PSMU [2,17,19]. With reference to the Bio-Ecological Model, we also want to explore if migration background influences PSMU among adolescents.…”
Section: Sociodemographic Factorsmentioning
confidence: 98%
See 4 more Smart Citations
“…The same study found that there was no association between family affluence and PSMU [19]. Findings on the relationship between gender and PSMU are varied; Bányai et al (2017) and Kircaburun et al (2019) found that girls are at a higher risk of PSMU than boys, whereas Paakkari et al (2021) did not find gender differences for PSMU [2,17,19]. With reference to the Bio-Ecological Model, we also want to explore if migration background influences PSMU among adolescents.…”
Section: Sociodemographic Factorsmentioning
confidence: 98%
“…Studies exist on the relationship between PSMU and sociodemographic characteristics, but the results are contradictory and, in some cases, not comparable. Schivinski et al (2020) found that age and gender did not significantly predict PSMU among (young) adults, whereas Paakkari et al (2021) found that PSMU was more prevalent in older adolescents compared with younger adolescents [12,19]. The same study found that there was no association between family affluence and PSMU [19].…”
Section: Sociodemographic Factorsmentioning
confidence: 99%
See 3 more Smart Citations